SRI RAMAKATHAMRTA SARA AN ANALYSIS - Iyer, Sriram Narainswamy (International Journal of Research -GRANTHAALAYAH, 2025)
As a testament to the benediction of Brahmā to Vālmīki that the story of Śrī Rāma would flourish as long as the mountains and rivers exist , innumerable literary works on the life of Śrī Rāma by the poets of yore as well as those of contemporary poets continue to sanctify this world. The huge stock of Rāmāyaṇa based poems is further enriched by the Śrī-Rāmakathāmṛta-sāra, a recently composed devotional poem in the form of an abridgement of the Rāmāyaṇa. The author of this work, Śrī Kṛṣṇa Premī Svāmigaḷ (1934-2023) was one of the greatest exponents of bhakti-sampradāya of the 20th and the early 21st century, who has to his credit, over a dozen Sanskrit works belonging to different genres such as kāvyas, stotras, philosophical texts etc. Each of these are noted for their poetic richness and the profound devotional fervour.